Provenance of lower Paleozoic sedimentary rocks in Tasmania and Waratah Bay, southern Victoria: constraints from detrital zircon hafnium isotopes and trace-element geochemistry. Issue 2 (17th February 2023) - Habib, U.; Meffre, S.; Berry, R.; Belousova, E.
Abstract: Nine Paleozoic sedimentary formations from western Tasmania and two from the Lachlan Orogen—one in northeast Tasmania and one in Waratah Bay in Victoria—contain detrital zircons that fall into major U–Pb age clusters at 2.0–1.4, 1.25–0.95 and 0.62–0.49 Ga. The zircon Th/U ratios and rare earth element (REE) patterns suggest a magmatic origin for detrital zircons in all these rock sequences. The REE geochemical signatures on bivariate discrimination diagrams indicate that most of the zircons originated in continental orogenic settings. The oldest group of zircons have a southwest Laurentian signature previously recognised from Proterozoic metasedimentary rocks in Tasmania. The 1.25–0.5 Ga zircons from all the samples have very similar εHfi values. They are not statistically different from those of typical Lachlan Orogen sandstones and resemble those in Rodinia and early Gondwana orogenic belts. The εHfi values of the Cambrian zircons within the Pioneer Sandstone are similar to the Mount Read Volcanics but cannot be distinguished on εHfi values from other sources in East Gondwana. The detrital zircon provenance of the Bear Gully Chert Bed at the base of the Digger Island Marlstone at Waratah Bay includes the west Tasmanian Proterozoic, the East Gondwana margin and the Macquarie Arc. This mixed provenance provides evidence for the late Cambrian docking of VanDieland with East Gondwana. KEY POINTS: New zircon Hf isotope data are reported for early Paleozoic sedimentary rocks in Tasmania and Waratah Bay, southern Victoria. The western Tasmania basement was the dominant source for Tasmanian sandstones and a minor source for the Lachlan Orogen sandstones on the northeast margin of VanDieland. The mixed provenance of the Bear Gully Chert supports a late Cambrian accretion of VanDieland to the East Gondwana margin. The youngest zircons in the Bear Gully Chert at Waratah Bay were potentially sourced from the Macquarie Arc.